Influence of Technological Treatments on the Functionality of Bifidobacterium lactis INL1, a Breast Milk-Derived Probiotic - Zacarías, María Florencia (2017)
Abstract: The aim of this study is to evaluate the influence of the technological processing on the functionality of the human breast milk probiotic strain Bifidobacterium lactis INL1. In vitro antagonistic activity of B. lactis INL1 was detected for Gram-positive and Gram-negative pathogens. B. lactis INL1 was administered to mice as fresh (F), frozen (Z), spray-dried (S), or lyophilized (L) culture. Immune parameters (IgA, IL-10, and IFN-γ) were determined and histological analysis was performed to assess functionality and protection capacity against Salmonella. In BALB/c mice, F and S cultures induced an increase in the number of IgA-producing cells in the small intestine and IL-10 levels were increased for L culture in the large intestine. In Swiss mice, B. lactis INL1 increased secretory-IgA levels in the small intestine before and after Salmonella infection, both as F or dehydrated culture. Also, an attenuation of damage in the intestinal epithelium and less inflammatory infiltrates were observed in animals that received F and S cultures, whereas in liver only F showed some effect. The anti-inflammatory effect was confirmed in both tissues by myeloperoxidase activity and by IFN-γ levels in the intestinal content. B. lactis INL1 showed inhibitory activity against pathogens and confirmed its probiotic potential in animal models. Technological processing of the probiotic strain affected its functionality. Practical Application: This work provides evidence about the influence of technology on the functionality of probiotics, which may help probiotics and functional food manufacturers to take processing into consideration when assessing the functionality of new strains.